2006
DOI: 10.1136/emj.2006.034652
|View full text |Cite
|
Sign up to set email alerts
|

A study of police operated dispatch to acute coronary syndrome cases arising from 112 emergency calls in Aarhus county, Denmark

Abstract: Background: The accuracy of the Danish police operated "112" emergency call system was studied. Dispatch of the anaesthesiologist staffed mobile emergency care unit (MECU) to acute coronary syndrome (ACS) cases was used as an indicator of accuracy of dispatch to life threatening emergencies. Methods: This was an observational cohort study of patients given a 112 system report of heart attack and patients with a provisional diagnosis of ACS made on scene by the MECU. Sensitivity, specificity, and positive predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…In a study on an emergency call centre from Amsterdam, 55% of calls classified as urgent proved to be non‐urgent (16). A recent Danish study in the same settings as in the present study showed a sensitivity of 75%, a specificity of 90% and a positive predictive value of 45% for the dispatch of a MECU to acute coronary syndrome (17). In a suburban city in the USA, the positive predictive value for detecting cardiac emergencies using priority dispatch was only 28.6% (5).…”
Section: Discussionsupporting
confidence: 55%
“…In a study on an emergency call centre from Amsterdam, 55% of calls classified as urgent proved to be non‐urgent (16). A recent Danish study in the same settings as in the present study showed a sensitivity of 75%, a specificity of 90% and a positive predictive value of 45% for the dispatch of a MECU to acute coronary syndrome (17). In a suburban city in the USA, the positive predictive value for detecting cardiac emergencies using priority dispatch was only 28.6% (5).…”
Section: Discussionsupporting
confidence: 55%
“…Cardiac arrest was found in only 4.9% of all patient contacts (53/1076, Figure 2 ) showing a massive overtriage of the BLS responders. This was expected as it has been described in two studies from our area: One found dispatch to acute coronary syndrome to have a positive predictive value of only 45% [ 16 ], the other a positive predictive value of only 39% when comparing persons classified as 'unconscious' in the dispatch message to the Glasgow Coma Scale-score upon arrival of the MECU at scene [ 19 ]. Emergency calls in Denmark are directed to the National Emergency Call Centre operated by the police (non-health care personnel) which may contribute to both over- and undertriage.…”
Section: Discussionmentioning
confidence: 61%
“…The EMS is a two tier system with ambulances manned with a paramedic and an emergency medical technician and a Mobile Emergency Care Unit (MECU) manned by an anaesthesiologist and a paramedic trained to assist the physician. The MECU is dispatched if life threatening situations are expected or if an ambulance needs assistance (rendez-vous with the ambulances) [ 16 ]. Response times (reception of dispatch message-to-arrival) for ambulances and the MECU averaged 6.7 and 9 minutes, respectively, in 2003 (most recent numbers prior to initiation of the study).…”
Section: Methodsmentioning
confidence: 99%
“…Ten years ago, a survey of prehospital care in the Nordic countries highlighted the former police-operated system as a weak link in Danish prehospital care [ 6 ]. A statement that was stressed by studies showing moderate to low accuracy in detection of acute coronary syndrome patients and patients with loss of consciousness [ 7 , 8 ]. The Danish EMCCs assess all incoming calls using a criteria-based dispatch protocol (the Danish Index for Emergency Care), which divides patients into five levels of emergency (A–E) based on their main symptoms [ 9 - 11 ].…”
Section: Introductionmentioning
confidence: 99%